2007
DOI: 10.1186/1472-6920-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based teaching is as good as face to face lecture-based teaching of evidence based medicine: a randomised controlled trial

Abstract: BackgroundAt postgraduate level evidence based medicine (EBM) is currently taught through tutor based lectures. Computer based sessions fit around doctors' workloads, and standardise the quality of educational provision. There have been no randomized controlled trials comparing computer based sessions with traditional lectures at postgraduate level within medicine.MethodsThis was a randomised controlled trial involving six postgraduate education centres in the West Midlands, U.K. Fifty five newly qualified fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
132
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 20 publications
5
132
0
3
Order By: Relevance
“…ELearning has been widely regarded as a new innovative methodology in effectively delivering knowledge and skills, in many disciplines, to large and scattered student communities (Davis et al 2006). ELearning refers to the use of electronic equipment, computer-based devices and internet based application to facilitate the process of teaching and learning (Nichols 2003;Benninck 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELearning has been widely regarded as a new innovative methodology in effectively delivering knowledge and skills, in many disciplines, to large and scattered student communities (Davis et al 2006). ELearning refers to the use of electronic equipment, computer-based devices and internet based application to facilitate the process of teaching and learning (Nichols 2003;Benninck 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that electronic-based learning appears to be effective as traditional instructor-led methods such as lectures in medical diverse education (Casebeer et al 2008;Curran et al 2006;Choules 2007;Lwoga 2012;Muhsin 2008;Davis 2006). For example, a study of the eLearning experiences of students in two universities in Ghana revealed that eLearning programmes were "more effective" in comparison to other methods of learning (Adanu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Findings support equal or slightly better performance in learners trained online than that in peers with face-to-face instruction. 14,15 Evidence of the efficacy of online training in SBIRT could allow broader curriculum implementation. To date, no studies have compared the 2 approaches in a SBIRT curriculum.…”
mentioning
confidence: 99%
“…[12] Many research studies regarding recently introduced asynchronous, computer-based learning which claims to offer advantage of being flexible, student-centered and improved utilization of resources, have failed to find any significant advantage over traditional classroom-based teaching. [13,14] Hence, didactic lectures still remain popular mode of teaching. It is associated with some weaknesses too, like lack of thought stimulation in large groups.…”
Section: Discussionmentioning
confidence: 99%